Mathematical Proof: The learning obstacles of pre-service mathematics teachers on transformation geometry - Noto, Muchamad Subali; Priatna, Nanang; Dahlan, Jarnawi Afgani (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2019)
Several studies related to mathematical proof have been done by many researchers on high-level materials, but not yet examined on the material of transformation geometry. The aim of this research is identification learning obstacles pre-service teachers on transformation geometry. This study is qualitative research; data were collected from interview sheets and test. There were four problems given to 9 pre-service mathematics teachers. The results of this research were as follows: learning obstacles related to the difficulty in applying the concept; related to visualize the geometry object; related to obstacles in determining principle; related to understanding the problem and related obstacles in mathematical proofs such as not understanding and unable to express a definition, not knowing to use the definition to construct the proof, not understanding the use of language and mathematical notation, not knowing how to start the proof.